A Review of Research on Strategic Differences and Debt Default Risk - Wu, Yuxiao; Ou, Qian (International Journal of Global Economics and Management, 2024)
In recent years, more and more scholars have been studying the impact of corporate strategy on debt default, so as to provide enterprises with more perfect strategy differentiation strategy, thus reducing the risk of corporate debt default, and improving the ability of preventing and coping with unforeseen shocks for enterprises with large strategic differentiation, thus reducing the operational risk of enterprises. In this paper, we look at the measurement indexes of strategic differences and debt default risk, as well as the influencing factors of debt default risk, the current status of the research on strategic differences and debt default risk, and put forward governance proposals for debt default.